TATA KELOLA KELEMBAGAAN DALAM PELAYANAN PEMBAYARAN PAJAK DAN BEA BALIK NAMA KENDARAAN BERMOTOR DI KANTOR BERSAMA SAMSAT (SISTEM ADMINISTRASI MANUNGGAL SATU ATAP) KABUPATEN PASAMAN TAHUN 2016-2017 - Rezy Agmadya Harika; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
As an organization engaged in the field of public services, especially registration and identification of motorized vehicles, payment of motor vehicle tax and donations of compulsory traffic accidents and office roads with Samsat also need to be monitored and controlled in order to always provide excellent service to the community as service users. Therefore researchers want to see institutional governance in the service of paying tax and transfer fees for motorized vehicles in the Pasaman District Samsat Office. The formulation of the problem from this study is how is institutional governance in the service of paying tax and transfer fees for motorized vehicles in the Joint Office of SAMSAT (One Roof Single Administration System) of Pasaman Regency in 2016-2017? and what factors are hindering institutional governance in the payment services for motor vehicle tax and transfer fees in the Joint Office of SAMSAT (One Roof Single Administration System) of Pasaman Regency in 2016-2017?. This study uses a qualitative research approach with a type of descriptive research. Data collection techniques used were interviews and documentation. Data analysis is limited to data processing techniques or facts obtained by developing categories that are relevant to the purpose of research and interpretation by referring to appropriate theories. The results showed that governance in the Pasaman regency samsat office was well-run, but there were only a number of obstacles, namely the use of information and communication technology that was not optimal, community participation was still lacking, work units were interrelated, and the image of the community in samsat it is convoluted and takes a long time.Keywords: Governance, Services, Vehicle Taxes